Micro-electricity enhanced adsorption lithium extraction method of low-salt lithium-containing system
By applying a microelectric field in the low-salt lithium-containing system, the adsorption and extraction performance of aluminum-based lithium adsorbent is improved, and the problems of low adsorption capacity and spontaneous desorption are solved, and efficient extraction of lithium in the low-salt lithium-containing system is achieved.
Patent Information
- Application Number
- CN202411613948.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
The existing aluminum-based lithium adsorbents have low adsorption capacity and spontaneous desorption in low-salt lithium-containing systems, making it difficult to efficiently extract lithium resources in low-salt systems.
By applying a microelectric field, the adsorption and extraction performance of aluminum-based lithium adsorbent in low-salt lithium-containing systems are improved. The specific steps include mixing aluminum-based lithium adsorbent with conductive agent and binder to form an electrode, applying a high voltage or high Current activates the electrode and then applies a low voltage or low current to adsorb lithium extraction.
The adsorption effect of aluminum-based lithium adsorbent in low-salt lithium-containing systems has been significantly improved, the problems of low adsorption capacity and spontaneous desorption are solved, and the efficient extraction of lithium in low-salt lithium-containing systems has been achieved.
Smart Images

Figure CN119464757A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium extraction by adsorption in a low-salt lithium-containing system, and more specifically to a method for lithium extraction by micro-electrically enhanced adsorption in a low-salt lithium-containing system. Background Art
[0002] Lithium is widely used in batteries, glass, ceramics, alloys and other fields due to its excellent physical and chemical properties. With the vigorous development of my country's new energy vehicle industry, the demand for lithium-ion batteries has also increased year by year. However, due to the difficulty and long cycle of lithium resource development, the growth rate of lithium production is much lower than the growth rate of battery shipments. Therefore, it is urgent to develop more lithium resources.
[0003] From the perspective of lithium resources, the global lithium resource supply system is divided into two major systems: lithium extraction from ores and lithium extraction from salt lakes. Among them, lithium resources in salt lake brine account for as high as 62.60%. Compared with traditional lithium extraction from ores, lithium extraction from salt lakes has the advantages of rich resources, simple process, low development cost and strong market competitiveness, making lithium extraction from salt lakes an important way to obtain lithium resources and the main source of lithium resource development. At present, domestic lithium extraction from salt lakes mainly adopts precipitation method, solvent extraction method, membrane separation method, salt gradient solar pool method, electrochemical method and adsorption method. The existing electrochemical lithium extraction method mainly uses potential to adjust the insertion / extraction of lithium ions in electrode materials, and generally achieves the lithium extraction effect by redox reaction in electrode materials. However, due to the high magnesium-lithium ratio, complex associated ions and low lithium concentration of my country's salt lake brine, the poor cycle stability of the working electrode for lithium extraction by electrochemical method and the dissolution phenomenon of electrode materials, the electrochemical method is not conducive to large-scale industrial development. In view of the characteristics of my country's salt lake brine, the adsorption method has been widely used due to its advantages such as simple process, low cost and stable cycle performance. In the adsorption method, aluminum-based lithium adsorbents have become the only mature industrial lithium adsorbents due to their high selectivity for lithium, desorption in neutral solutions, no dissolution loss, good cycle stability and other significant advantages. They are widely used in lithium extraction from salt lakes. However, with the continuous development and utilization of lithium resources, salt lake resources will inevitably be depleted.
[0004] There is a lot of lithium in low-salt systems such as seawater, oilfield wastewater, wastewater from lithium mining, and waste lithium-ion battery leachate. In particular, there are about 230 billion tons of lithium resources in seawater, which is more than 5,000 times the current global lithium resources in lithium mines and salt lakes. Efficient recovery / extraction of lithium resources in these low-salt lithium-containing systems can provide protection and support for the rapid development of my country's new energy, aerospace, metallurgy and medical industries. However, when aluminum-based lithium adsorbents, the only mature industrialized lithium adsorbents, are applied to the adsorption and extraction of lithium in these low-salt lithium-containing systems, there is still a disadvantage of low adsorption capacity. In particular, for low-salt lithium-containing systems, due to the low ion concentration, the adsorption power is insufficient, so the adsorption effect of aluminum-based lithium adsorbents is greatly reduced. Therefore, it is particularly important to develop adsorption and lithium extraction methods suitable for low-salt lithium-containing systems for extracting lithium from these systems. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for micro-electrically enhanced adsorption and extraction of lithium in a low-salt lithium-containing system. In the method of the present invention, the adsorption and extraction performance of aluminum-based lithium adsorbents in low-salt lithium-containing systems is improved by applying a micro-electric field, solving the problems of low adsorption capacity and spontaneous desorption of aluminum-based lithium adsorbents under low-salt conditions.
[0006] The object of the present invention is achieved by the following technical solution: A method for extracting lithium by micro-electro-enhanced adsorption in a low-salt lithium-containing system, comprising the following steps:
[0007] (1) mixing an aluminum-based lithium adsorbent, a binder, a conductive agent, and an organic solvent to obtain a uniform slurry;
[0008] (2) uniformly coating the slurry on a conductive substrate material, and then removing the organic solvent to obtain an aluminum-based lithium adsorbent electrode;
[0009] (3) The aluminum-based lithium adsorbent electrode is used as the cathode of the micro-electric device, and the conductive electrode is used as the anode. After applying high voltage or high current to activate the aluminum-based lithium adsorbent electrode, a low voltage or low current is applied to adsorb and extract lithium from the low-salt lithium-containing system;
[0010] (4) Disconnect the power supply, and desorb the aluminum-based lithium adsorbent electrode in a desorption solution to obtain a lithium-containing solution.
[0011] The general expression of the aluminum-based lithium adsorbent is LiX·mAl(OH)3·nH2O. In a preferred embodiment of the present invention, the aluminum-based lithium adsorbent includes at least one of LiCl·mAl(OH)3·nH2O, LiBr·mAl(OH)3·nH2O, Li2SO4·mAl(OH)3·nH2O, and Li2CO3·mAl(OH)3·nH2O. In a preferred embodiment of the present invention, the aluminum-based lithium adsorbent is LiCl·2Al(OH)3·nH2O.
[0012] In a preferred embodiment of the present invention, the binder includes at least one of polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene, and water-based polyacrylate.
[0013] In a preferred embodiment of the present invention, the conductive agent includes at least one of carbon black, acetylene black, graphite, carbon fiber, carbon nanotube, graphene, and composite conductive paste.
[0014] In a preferred embodiment of the present invention, the organic solvent includes at least one of N-methylpyrrolidone, N-ethylpyrrolidone, N-vinylpyrrolidone, dimethylformamide and dimethylacetamide.
[0015] In a preferred embodiment of the present invention, the weight ratio of organic solvent: aluminum-based lithium adsorbent: binder: conductive agent is 30-34:8-10:1-2:1-2. In a preferred embodiment of the present invention, the weight ratio of organic solvent: aluminum-based lithium adsorbent: binder: conductive agent is 30-34:8-10:1-2:2; 30-34:8-10:1-2:1.5; 30-34:8-10:1-2:1; 30-34:8-10:2:1-2; 30-34:8-10:1.5:1-2; 30-34:8-10 :1:1-2;30-34:10:1-2:1-2;30-34:9:1-2:1-2;30-34:8:1-2:1-2;34:8-10:1-2:1-2;33:8-10:1-2:1-2;32:8-10:1-2:1-2;31:8-10:1-2:1-2;30:8-10:1-2:1-2.
[0016] In a preferred embodiment of the present invention, the aluminum-based lithium adsorbent, the binder, the conductive agent, and the organic solvent are mixed by stirring and / or ultrasound to obtain a uniform slurry. In some embodiments, the stirring time is preferably 2-24 hours, such as 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours. In some embodiments, the ultrasonic time is preferably 2-12 hours, such as 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours.
[0017] In a preferred embodiment of the present invention, the conductive matrix material is at least one of an inert metal conductive material and a non-metal conductive material. The inert metal conductive material includes but is not limited to gold, silver, platinum, palladium, rhodium, iridium, and titanium; the non-metal conductive material includes but is not limited to graphite, carbon cloth, organic conductive polymer, carbon felt, and conductive ceramics.
[0018] Optionally, before the slurry is uniformly coated on the conductive substrate material, the conductive substrate material can be placed in a cleaning solution for cleaning to remove impurities such as oil stains on the surface of the conductive substrate material. In some embodiments, the conductive substrate material is placed in water and an organic solvent for ultrasonic treatment in sequence for cleaning. Among them, the organic solvent includes but is not limited to at least one of methanol, ethanol, acetone, and chloroform. The ultrasonic treatment time is preferably 10-120 minutes, for example 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes, 110 minutes, 120 minutes.
[0019] In a preferred embodiment of the present invention, the organic solvent is removed by heating. The heating can be carried out in an oven or a muffle furnace. In some embodiments, the heating temperature is preferably 30-150°C, such as 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C. The heating time is preferably 0.5-10h, such as 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h.
[0020] In a preferred embodiment of the present invention, the micro-electric device includes a solution pool, an electrode, a power supply, a peristaltic pump, and a stirrer. In some embodiments, the solution pool is preferably square, circular, pentagonal, hexagonal, or irregular in shape. The aluminum-based lithium adsorbent electrode is a lithium extraction electrode connected to the negative electrode of the power supply, and the conductive electrode is connected to the positive electrode of the power supply as a counter electrode, and a constant current and / or a constant voltage are applied to enhance the adsorption and lithium extraction performance of the aluminum-based lithium adsorbent in a low-salt lithium-containing system.
[0021] In a preferred embodiment of the present invention, the conductive electrode can be at least one of an inert metal conductive material and a non-metal conductive material. In some embodiments, the inert metal conductive material includes but is not limited to gold, silver, platinum, palladium, rhodium, iridium, and titanium; the non-metal conductive material includes but is not limited to graphite, carbon cloth, organic conductive polymer, carbon felt, and conductive ceramics.
[0022] In a preferred embodiment of the present invention, the total salt concentration in the low-salt lithium-containing system is 1-80 g / L. For example, the total salt concentration is preferably 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L.
[0023] In a preferred embodiment of the present invention, the cation in the low-salt lithium-containing system is Na + , K + Mg 2+ , Ca 2+ One or more of; the anion is Cl - Br - 、F - 、NO2 - 、NO3 - 、CO3 2- 、SO3 2- 、SO4 2- PO4 3- One or more of .
[0024] In a preferred embodiment of the present invention, the lithium ion concentration in the low-salt lithium-containing system is 0.001-1.0 g / L. For example, the lithium concentration is preferably 0.001 g / L, 0.005 g / L, 0.01 g / L, 0.05 g / L, 0.1 g / L, 0.15 g / L, 0.2 g / L, 0.25 g / L, 0.3 g / L, 0.35 g / L, 0.4 g / L, 0.45 g / L, 0.5 g / L, 0.55 g / L, 0.6 g / L, 0.65 g / L, 0.7 g / L, 0.75 g / L, 0.8 g / L, 0.85 g / L, 0.9 g / L, 0.95 g / L, and 1.0 g / L.
[0025] Optionally, the aluminum-based lithium adsorbent electrode is pre-desorbed before use, and the aluminum-based lithium adsorbent electrode is placed in a pre-desorption solution, connected to the positive electrode of a power source, and operated at a constant current or constant voltage for a period of time. The voltage can be 0.01-10V, for example, 0.01V, 0.05V, 0.1V, 0.5V, 1.0V, 1.5V, 2.0V, 2.5V, 3.0V, 2.5V, 4.0V, 4.5V, 5.0V, 5.5V, 6.0V, 6.5V, 7.0V, 7.5V, 8.0V, 8.5V, 9.0V, 9.5V, 10.0V; the current can be 0.001-1.0A, for example, 0.001A, 0.005A, 0.01A, 0.05A, 0.1A, 0.5A, 1.0A; the operating time can be 10-60min, for example, 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min, 60min. Under the action of voltage or current, lithium ions in the aluminum-based lithium adsorbent electrode are partially or completely deintercalated to form lithium ion holes.
[0026] In a preferred embodiment of the present invention, the pre-desorption liquid can be at least one of deionized water, ultrapure water, lithium-containing solution, ethanol, and propanol. The ratio of the aluminum-based lithium adsorbent electrode to the pre-desorption liquid is 1 m2 :(0.1-4)L, for example, preferably 1m 2 :0.1L、1m 2 :0.2L、1m 2 :0.4L、1m 2 :0.6L、1m 2 :0.8L、1m 2 :1L, 1m 2 :1.5L、1m 2 :2L、1m 2 :2.5L、1m 2 :3L、1m 2 :3.5L, 1m 2 :4L.
[0027] In a preferred embodiment of the present invention, a high voltage or a high current is applied to activate the aluminum-based lithium adsorbent electrode. The applied high voltage may be 20-80V, for example, 20V, 25V, 30V, 35V, 40V, 45V, 50V, 55V, 60V, 65V, 70V, 75V, 80V; the applied high current may be 5-10A, for example, 5A, 6A, 7A, 8A, 9A, 10A; the power-on time may be 1-10min, for example, 1min, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min. Not bound by theory, the main plate layer of the aluminum-based lithium adsorbent electrode carries a positive charge, which inhibits the adsorption of lithium ions. Under the action of high voltage or high current, the aluminum-based lithium adsorbent electrode carries a negative charge, which reduces the electrostatic resistance of the adsorbed lithium ions.
[0028] In a preferred embodiment of the present invention, after activating the aluminum-based lithium adsorbent electrode, a low voltage or a low current is applied to adsorb and extract lithium from the low-salt lithium-containing system. The applied low voltage may be 0.01-10V, for example, 0.01V, 0.05V, 0.1V, 0.5V, 1.0V, 1.5V, 2.0V, 2.5V, 3.0V, 3.5V, 4.0V, 4.5V, 5.0V, 5.5V, 6.0V, 6.5V, 7.0V, 7.5V, 8.0V, 8.5V, 9.0V, 9.5V, 10.0V; the applied low current may be 0.001-1.0A, for example, 0.001A, 0.005A, 0.01A, 0.05A, 0.1A, 0.5, 1.0A; the power-on time may be 20-120min, for example, 20min, 40min, 60min, 80min, 100min, 120min. Not bound by theory, under the action of the micro-electric field, the anions and cations in the low-salt lithium-containing system migrate directionally to the vicinity of the electrode surface and form a double-layer region with a local high ion concentration on the electrode surface, thereby enhancing the adsorption kinetics of the aluminum-based lithium adsorbent electrode, thereby improving the adsorption and lithium extraction performance of the aluminum-based lithium adsorbent electrode in the low-salt lithium-containing system.
[0029] In a preferred embodiment of the present invention, stirring is performed while adsorbing the low-salt lithium-containing system, and the stirring speed can be 100-800rpm, for example, 100rpm, 150rpm, 200rpm, 250rpm, 300rpm, 350rpm, 400rpm, 450rpm, 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, 750rpm, 800rpm.
[0030] In a preferred embodiment of the present invention, the desorption liquid can be at least one of deionized water, ultrapure water, lithium-containing solution, ethanol, and propanol. In a preferred embodiment of the present invention, the pH of the desorption liquid is 5.5-7.5, for example, 5.5, 6.0, 6.5, 7.0, 7.5.
[0031] In a preferred embodiment of the present invention, nanobubbles are added to the desorption liquid. The surface of the nanobubbles is negatively charged and can attract positive ions, thereby strengthening the desorption of lithium ions. The nanobubbles can be prepared directly in the solution using ultrasonic cavitation, hydrodynamic cavitation or membrane method. The nanobubbles can be various types of nanobubbles, including but not limited to one or more of oxygen nanobubbles, nitrogen nanobubbles, carbon dioxide nanobubbles, air nanobubbles, argon nanobubbles, and ozone nanobubbles. The diameter of the nanobubbles is generally between 10-1000nm, for example, 10nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm.
[0032] In a further preferred embodiment of the present invention, the micro-electric device can be rinsed after desorption, wherein the rinsing liquid can be at least one of deionized water, ultrapure water, ethanol, and propanol. In some embodiments, the pH of the rinsing liquid can be 5.5-7.5, for example, 5.5, 6.0, 6.5, 7.0, 7.5.
[0033] In a further preferred embodiment of the present invention, the aluminum-based lithium adsorbent electrode is dried after rinsing. In some preferred embodiments, the drying temperature can be 40-150°C, for example, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150°C; the drying time can be 0.5-12h, for example, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12h.
[0034] The beneficial effects of the present invention are:
[0035] The micro-electric enhanced adsorption and lithium extraction method of the present invention is essentially different from the existing electrochemical lithium extraction method, because no redox reaction occurs in the method of the present invention, but only the electric field is used to enhance the local ion concentration on the electrode surface. Not bound by theory, under the action of the electric field, the anions and cations in the low-salt lithium-containing system migrate to the vicinity of the electrode surface, and form a double electric layer region with a local high ion concentration on the electrode surface, which enhances the adsorption power of the aluminum-based lithium adsorbent electrode, thereby improving the adsorption and lithium extraction performance of the aluminum-based lithium adsorbent electrode in the low-salt lithium-containing system.
[0036] In the method of the present invention, the voltage or current intensity applied by the power supply during adsorption and extraction of lithium is low, thereby reducing energy consumption. In the method of the present invention, there is no material dissolution phenomenon, and the cycle stability performance is good. In the method of the present invention, desorption can be performed by a desorption liquid, thereby saving the energy required for electrochemical desorption.
[0037] The method of the present invention is applicable to low-salt lithium-containing solutions, can greatly enhance the adsorption effect of aluminum-based lithium adsorbent on lithium in low-salt lithium-containing systems, achieve efficient extraction of lithium in low-salt lithium-containing systems, broaden the application scenarios of aluminum-based lithium adsorbents, and the method is simple to operate, has no secondary pollution, and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a scanning electron microscope image of the aluminum-based lithium adsorbent electrode in Example 1.
[0039] Figure 2 1 and 2 are X-ray diffraction patterns of the aluminum-based lithium adsorbent and the aluminum-based lithium adsorbent electrode in Example 1.
[0040] Figure 3 The lithium ion adsorption kinetic curves of the aluminum-based lithium adsorbent electrode of Example 3 and Comparative Example 3 in a low-salt lithium-containing solution.
[0041] Figure 4 The adsorption capacity of the aluminum-based lithium adsorbent electrode of Example 1 and Comparative Example 1 in the cyclic lithium extraction experiment with power on and without power on. DETAILED DESCRIPTION
[0042] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be noted that the embodiments are exemplary and non-restrictive. Based on the embodiments of the present invention, those skilled in the art may make many modifications or improvements, which all belong to the scope of protection of the present invention.
[0043] Unless otherwise specified, all technical and scientific terms used herein have the meanings commonly understood by those of ordinary skill in the art to which the invention belongs. The terms used in the specification of the present invention are only for describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0044] Unless otherwise specified, the experimental methods used in the examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.
[0045] Example 1
[0046] LiCl·2Al(OH)3·nH2O, polyvinylidene fluoride, carbon black, and dimethylformamide were mixed in a weight ratio of 9:1:1:32 and stirred for 24 hours to obtain a uniform slurry.
[0047] The titanium sheet was cut into 5 cm × 5 cm size, ultrasonically treated in 300 mL of deionized water at room temperature for 10 minutes, and then ultrasonically treated in 300 mL of anhydrous ethanol for 10 minutes to remove organic matter and other impurities on the surface. The slurry was evenly coated on the titanium sheet using a scraper until a film with uniform thickness and no obvious holes was formed. Then it was heated in an oven at 100 ° C for 5 hours to remove the organic solvent and form a film with a thickness of 400 μm on the titanium sheet, thereby obtaining an aluminum-based lithium adsorbent electrode.
[0048] The aluminum-based lithium adsorbent electrode was placed in deionized water at a ratio of 1 m 2 :4L, connected to the positive electrode of the power supply, the pre-desorption voltage is 0.01V, run for 30min, so that the lithium in the aluminum-based lithium adsorbent is deintercalated under the action of the electric field, generating a large number of lithium ion holes. Then, the aluminum-based lithium adsorbent electrode is used as the cathode in the micro-electric device and connected to the negative electrode of the power supply, the conductive electrode (titanium sheet) is used as the counter electrode and connected to the positive electrode of the power supply, and the self-prepared low-salt lithium-containing solution is pumped into the solution pool of the micro-electric device by a peristaltic pump. The stirring speed is set to 200rpm, first apply a high voltage of 20V, the power-on time is 4min, and then apply a low voltage of 5.0V. After 45min of power-on, take a sample, and after dilution, use ICP-OES to determine the lithium content in the solution to obtain the equilibrium adsorption capacity q1.
[0049] Disconnect the power supply, place the aluminum-based lithium adsorbent electrode in a desorption solution (ultrapure water doped with air nanobubbles with a diameter of 400nm) for desorption, and obtain a lithium-containing solution. After desorption, rinse the micro-electric device with anhydrous ethanol, and then dry the aluminum-based lithium adsorbent electrode at 120°C for 1h. The dried aluminum-based lithium adsorbent electrode can be recycled, and 5 cycles of adsorption and lithium extraction experiments are carried out in the same self-prepared low-salt lithium-containing solution.
[0050] Table 1: Composition of self-prepared low-salt lithium-containing solution
[0051]
[0052] Example 2
[0053] LiCl·2Al(OH)3·nH2O: polyvinylidene fluoride: acetylene black: dimethylformamide were mixed in a weight ratio of 9:1:1:31 and stirred for 24 hours to obtain a uniform slurry.
[0054] The titanium sheet was cut into 5 cm × 5 cm size, ultrasonically treated in 300 mL of deionized water at room temperature for 10 minutes, and then ultrasonically treated in 300 mL of anhydrous ethanol for 10 minutes to remove organic matter and other impurities on the surface. The slurry was evenly coated on the titanium sheet using a scraper until a film with uniform thickness and no obvious holes was formed. Then it was heated in an oven at 150 ° C for 3 hours to remove the organic solvent and form a film with a thickness of 400 μm on the titanium sheet, thereby obtaining an aluminum-based lithium adsorbent electrode.
[0055] The aluminum-based lithium adsorbent electrode was placed in a lithium-containing solution at a ratio of 1 m 2 :3L, connected to the positive electrode of the power supply, the pre-desorption current is 0.01A, run for 40min, so that the lithium in the aluminum-based lithium adsorbent is deintercalated under the action of the electric field, generating a large number of lithium ion holes. Then, the aluminum-based lithium adsorbent electrode is used as the cathode in the micro-electric device and connected to the negative electrode of the power supply, the conductive electrode (titanium sheet) is used as the counter electrode and connected to the positive electrode of the power supply, and the self-prepared low-salt lithium-containing solution is pumped into the solution pool of the micro-electric device by a peristaltic pump. The stirring speed is set to 200rpm, and a high voltage of 80V is applied first, and the power-on time is 1min, and then a low voltage of 8.0V is applied. Samples are taken after 45min of power-on, and the lithium content in the solution is determined by ICP-OES after dilution to obtain the equilibrium adsorption capacity q2.
[0056] Disconnect the power supply, place the aluminum-based lithium adsorbent electrode in a desorption solution (deionized water mixed with 200nm diameter carbon dioxide bubbles) for desorption to obtain a lithium-containing solution. After desorption, rinse the micro-electric device with anhydrous ethanol, and then dry the aluminum-based lithium adsorbent electrode at 120°C for 1h. The dried aluminum-based lithium adsorbent electrode can be recycled.
[0057] Table 2: Composition of self-prepared low-salt lithium-containing solution
[0058]
[0059] Example 3
[0060] LiCl·2Al(OH)3·nH2O: polyvinylidene fluoride: acetylene black: dimethylformamide were mixed in a weight ratio of 9:1:1:28 and stirred for 24 h to obtain a uniform slurry.
[0061] The titanium sheet was cut into 5 cm × 5 cm size, ultrasonically treated in 300 mL of deionized water at room temperature for 10 minutes, and then ultrasonically treated in 300 mL of anhydrous ethanol for 10 minutes to remove organic matter and other impurities on the surface. The slurry was evenly coated on the titanium sheet using a scraper until a film with uniform thickness and no obvious holes was formed. Then it was heated in an oven at 100 ° C for 8 hours to remove the organic solvent and form a film with a thickness of 400 μm on the titanium sheet, thereby obtaining an aluminum-based lithium adsorbent electrode.
[0062] The aluminum-based lithium adsorbent electrode was placed in a lithium-containing solution at a ratio of 1 m 2 :3L, connected to the positive electrode of the power supply, the pre-desorption voltage is 0.01V, and it runs for 40min, so that the lithium in the aluminum-based lithium adsorbent is deintercalated under the action of the electric field, generating a large number of lithium ion holes. However, the aluminum-based lithium adsorbent electrode is used as the cathode in the micro-electric device and connected to the negative electrode of the power supply, and the conductive electrode (titanium sheet) is used as the counter electrode and connected to the positive electrode of the power supply. The self-prepared low-salt lithium-containing solution is pumped into the solution pool of the micro-electric device by a peristaltic pump, and the stirring speed is set to 300rpm. A high voltage of 40V is applied first, and the power-on time is 2min, and then a low voltage of 10.0V is applied. Samples are taken after the power-on time is 10, 30, 45, 60, and 120min. After dilution, the lithium content in the solution is determined by ICP-OES, and the equilibrium adsorption capacity q3 is obtained.
[0063] The power supply is disconnected, and the aluminum-based lithium adsorbent electrode is placed in a desorption solution (deionized water mixed with nitrogen nanobubbles with a diameter of 400 nm) for desorption to obtain a lithium-containing solution. After desorption, the micro-electric device is rinsed with anhydrous ethanol, and the aluminum-based lithium adsorbent electrode is dried at 100°C for 1.5 hours. The dried aluminum-based lithium adsorbent electrode can be recycled.
[0064] Table 3 Composition of self-prepared low-salt lithium-containing solution
[0065]
[0066] Example 4
[0067] LiCl·2Al(OH)3·nH2O, polyvinylidene fluoride, carbon black, and dimethylformamide were mixed in a weight ratio of 9:1:1:32 and stirred for 24 hours to obtain a uniform slurry.
[0068] The titanium sheet was cut into 5 cm × 5 cm size, ultrasonically treated in 300 mL of deionized water at room temperature for 10 minutes, and then ultrasonically treated in 300 mL of anhydrous ethanol for 10 minutes to remove organic matter and other impurities on the surface. The slurry was evenly coated on the titanium sheet using a scraper until a film with uniform thickness and no obvious holes was formed. Then it was heated in an oven at 100 ° C for 5 hours to remove the organic solvent and form a film with a thickness of 400 μm on the titanium sheet, thereby obtaining an aluminum-based lithium adsorbent electrode.
[0069] The aluminum-based lithium adsorbent electrode was placed in ultrapure water at a ratio of 1 m 2:4L, connected to the positive electrode of the power supply, the pre-desorption current is 0.01A, run for 30min, so that the lithium in the aluminum-based lithium adsorbent is deintercalated under the action of the electric field, generating a large number of lithium ion holes. Then, the aluminum-based lithium adsorbent electrode is used as the cathode in the micro-electric device and connected to the negative electrode of the power supply, the conductive electrode (titanium sheet) is used as the counter electrode and connected to the positive electrode of the power supply, and the Qaidam oilfield wastewater (lithium content is about 0.21g / L, total salt concentration is about 50.6g / L) is pumped into the solution pool of the micro-electric device by a peristaltic pump, the stirring speed is set to 200rpm, a high voltage of 50V is applied first, the power-on time is 2min, and then a low voltage of 5.0V is applied. Samples are taken after 45min of power-on, and the lithium content in the solution is determined by ICP-OES after dilution, and the equilibrium adsorption capacity q4 is obtained.
[0070] Disconnect the power supply, place the aluminum-based lithium adsorbent electrode in a desorption solution (deionized water mixed with air nanobubbles with a diameter of 800nm) for desorption, and obtain a lithium-containing solution. After desorption, rinse the micro-electric device with anhydrous ethanol, and then dry the aluminum-based lithium adsorbent electrode at 120°C for 1h. The dried aluminum-based lithium adsorbent can be recycled.
[0071] Example 5
[0072] LiCl·2Al(OH)3·nH2O: polyvinylidene fluoride: acetylene black: dimethylformamide were mixed in a weight ratio of 9:1:1:31 and stirred for 24 hours to obtain a uniform slurry.
[0073] The titanium sheet was cut into 5 cm × 5 cm size, ultrasonically treated in 300 mL of deionized water at room temperature for 10 minutes, and then ultrasonically treated in 300 mL of anhydrous ethanol for 10 minutes to remove organic matter and other impurities on the surface. The slurry was evenly coated on the titanium sheet using a scraper until a film with uniform thickness and no obvious holes was formed. Then it was heated in an oven at 150 ° C for 3 hours to remove the organic solvent and form a film with a thickness of 400 μm on the titanium sheet, thereby obtaining an aluminum-based lithium adsorbent electrode.
[0074] The aluminum-based lithium adsorbent electrode was placed in a lithium-containing solution at a ratio of 1 m 2:4L, connected to the positive electrode of the power supply, the pre-desorption voltage is 0.01V, and it runs for 30min, so that the lithium in the aluminum-based lithium adsorbent is deintercalated under the action of the electric field, generating a large number of lithium ion holes. Then, the aluminum-based lithium adsorbent electrode is used as the cathode in the micro-electric device and connected to the negative electrode of the power supply, and the conductive electrode (titanium sheet) is used as the counter electrode and connected to the positive electrode of the power supply. The lithium mine wastewater (lithium content is about 0.31g / L, and the total salt concentration is about 46.1g / L) is pumped into the solution pool of the micro-electric device by a peristaltic pump. The stirring speed is set to 200rpm, and a high voltage of 60V is applied first, and the power-on time is 1min, and then a low voltage of 8.0V is applied. After 45min of power-on, a sample is taken, and the lithium content in the solution is determined by ICP-OES after dilution, and the equilibrium adsorption capacity q5 is obtained.
[0075] Disconnect the power supply, place the aluminum-based lithium adsorbent electrode in a desorption solution (deionized water mixed with air nanobubbles with a diameter of 50nm) for desorption, and obtain a lithium-containing solution. After desorption, rinse the micro-electric device with anhydrous ethanol, and then dry the aluminum-based lithium adsorbent electrode at 120°C for 1h. The dried aluminum-based lithium adsorbent can be recycled.
[0076] Example 6
[0077] LiCl·2Al(OH)3·nH2O: polyvinylidene fluoride: acetylene black: dimethylformamide were mixed in a weight ratio of 9:1:1:28 and stirred for 24 h to obtain a uniform slurry.
[0078] The titanium sheet was cut into 5 cm × 5 cm size, ultrasonically treated in 300 mL of deionized water at room temperature for 10 minutes, and then ultrasonically treated in 300 mL of anhydrous ethanol for 10 minutes to remove organic matter and other impurities on the surface. The slurry was evenly coated on the titanium sheet using a scraper until a film with uniform thickness and no obvious holes was formed. Then it was heated in an oven at 100 ° C for 6 hours to remove the organic solvent and form a film with a thickness of 400 μm on the titanium sheet, thereby obtaining an aluminum-based lithium adsorbent electrode.
[0079] The aluminum-based lithium adsorbent electrode was placed in a lithium-containing solution at a ratio of 1 m 2:3L, connected to the positive electrode of the power supply, the pre-desorption voltage is 0.01A, run for 30min, so that the lithium in the aluminum-based lithium adsorbent is deintercalated under the action of the electric field, generating a large number of lithium ion holes. Then, the aluminum-based lithium adsorbent electrode is used as the cathode in the micro-electric device and connected to the negative electrode of the power supply, the conductive electrode (titanium sheet) is used as the counter electrode and connected to the positive electrode of the power supply, and the waste lithium battery leaching solution (lithium content is about 1.0g / L, total salt concentration is about 51g / L) is pumped into the solution pool of the micro-electric device by a peristaltic pump, the stirring speed is set to 300rpm, first apply a high voltage of 40V, the power-on time is 2min, and then apply a low voltage of 10.0V. Samples are taken after 45min of power-on, and the lithium content in the solution is determined by ICP-OES after dilution to obtain the equilibrium adsorption capacity q6.
[0080] The power supply is disconnected, and the aluminum-based lithium adsorbent electrode is placed in a desorption solution (deionized water mixed with air nanobubbles with a diameter of 400 nm) for desorption to obtain a lithium-containing solution. After desorption, the micro-electric device is rinsed with anhydrous ethanol, and the aluminum-based lithium adsorbent electrode is dried at 120°C for 1 hour. The dried aluminum-based lithium adsorbent electrode can be recycled.
[0081] Comparative Example 1
[0082] The difference between Comparative Example 1 and Example 1 is that the power supply is not powered on, and the remaining steps are the same as Example 1. The equilibrium adsorption capacity is q1 * .
[0083] Comparative Example 2
[0084] The difference between Comparative Example 2 and Example 2 is that the power supply is not powered on, and the remaining steps are the same as Example 2. The equilibrium adsorption capacity is q2 * .
[0085] Comparative Example 3
[0086] The difference between Comparative Example 3 and Example 3 is that the power supply is not powered on, and the remaining steps are the same as Example 3. The equilibrium adsorption capacity is q3 * .
[0087] Comparative Example 4
[0088] The difference between Comparative Example 4 and Example 4 is that the power supply is not powered on, and the remaining steps are the same as Example 4. The equilibrium adsorption capacity is q4 * .
[0089] Comparative Example 5
[0090] The difference between Comparative Example 5 and Example 5 is that the power supply is not powered on, and the remaining steps are the same as Example 5. The equilibrium adsorption capacity is q5 * .
[0091] Comparative Example 6
[0092] The difference between Comparative Example 6 and Example 6 is that the power supply is not powered on, and the remaining steps are the same as Example 6. The equilibrium adsorption capacity is q6 * .
[0093] Results Analysis
[0094] The lithium adsorption capacities in Examples 1-6 and Comparative Examples 1-6 are shown in Table 4 below.
[0095] Table 4: Equilibrium adsorption capacity of Examples 1-6 and Comparative Examples 1-6 in low-salt lithium-containing solutions
[0096]
[0097] It can be seen from Table 4 that the equilibrium adsorption capacity of Comparative Examples 1-6 in low-salt lithium-containing solutions is relatively low, only 55-310 mg / m 2 , while the equilibrium adsorption capacity of Examples 1-6 subjected to micro-electric strengthening in low-salt lithium-containing solutions reached 220-715 mg / m 2 The adsorption amount was greatly improved, indicating that micro-electro-enhancement effectively improved the adsorption performance of aluminum-based lithium adsorbent for lithium in low-salt lithium-containing solution.
[0098] Figure 1 is a scanning electron microscope image of the aluminum-based lithium adsorbent electrode in Example 1. Figure 1 It can be seen that the aluminum-based lithium adsorbent is evenly distributed on the titanium sheet and forms nanosheet clusters on the surface. The conductive agent and the binder do not change the morphology of the aluminum-based lithium adsorbent.
[0099] Figure 2 is the X-ray diffraction pattern of the aluminum-based lithium adsorbent and the aluminum-based lithium adsorbent electrode in Example 1. Figure 2 It can be seen that the aluminum-based lithium adsorbent has a good crystal shape, which is consistent with the standard structure of LiCl·2Al(OH)3·nH2O, does not contain other impurity phases, and only has obvious diffraction peaks in the (003), (006) and (009) directions. The conductive agent and binder do not change the structure of the aluminum-based lithium adsorbent.
[0100] Figure 3 The lithium ion adsorption kinetic curves of the aluminum-based lithium adsorbent electrode of Example 3 and Comparative Example 3 in a low-salt lithium-containing solution. Figure 3 It can be seen that the adsorption equilibrium is reached 45 minutes after power is turned on, and the equilibrium adsorption capacity q3 is 573.3 mg / m 2 , the adsorption capacity is enhanced by about 3.30 times compared with that without power supply; Figure 3 It can be seen that when no power is applied, the adsorption equilibrium is reached after 60 minutes, and the equilibrium adsorption capacity q 3* Only 173.8 mg / m 2 .
[0101] Figure 4 The adsorption capacity of the aluminum-based lithium adsorbent electrode of Example 1 and Comparative Example 1 in the cyclic lithium extraction experiment under power and no power. Figure 4 It can be seen that the adsorption capacity of lithium for the powered / unpowered aluminum-based lithium adsorbent electrode remains relatively stable within 5 cycles, and the cycle performance is good; when powered, the adsorption capacity of lithium is greatly improved, reaching up to 4.5 times the adsorption capacity when not powered.
[0102] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A method for extracting lithium by micro-electrically enhanced adsorption in a low-salt lithium-containing system, comprising the following steps: (1) mixing an aluminum-based lithium adsorbent, a binder, a conductive agent, and an organic solvent to obtain a uniform slurry; (2) uniformly coating the slurry on a conductive substrate material, and then removing the organic solvent to obtain an aluminum-based lithium adsorbent electrode; (3) The aluminum-based lithium adsorbent electrode is used as the cathode of the micro-electric device, and the conductive electrode is used as the anode. After applying high voltage or high current to activate the aluminum-based lithium adsorbent electrode, a low voltage or low current is applied to adsorb and extract lithium from the low-salt lithium-containing system; (4) Disconnect the power supply, and desorb the aluminum-based lithium adsorbent electrode in a desorption solution to obtain a lithium-containing solution.
2. The method according to claim 1, wherein the aluminum-based lithium adsorbent comprises at least one of LiCl·mAl(OH)3·nH2O, LiBr·mAl(OH)3·nH2O, Li2SO4·mAl(OH)3·nH2O, Li2CO3·mAl(OH)3·nH2O; and / or The binder includes at least one of polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene, and water-based polyacrylate; and / or The conductive agent includes at least one of carbon black, acetylene black, graphite, carbon fiber, carbon nanotube, graphene, and composite conductive paste; and / or The organic solvent includes at least one of N-methylpyrrolidone, N-ethylpyrrolidone, N-vinylpyrrolidone, dimethylformamide and dimethylacetamide.
3. The method according to claim 1, wherein the weight ratio of organic solvent: aluminum-based lithium adsorbent: binder: conductive agent is 30-34: 8-10: 1-2: 1-2; The aluminum-based lithium adsorbent, the binder, the conductive agent and the organic solvent are mixed by stirring and / or ultrasound; wherein the stirring time is 2-24 hours, and / or the ultrasound time is 2-12 hours.
4. The method according to claim 1, wherein the conductive matrix material is at least one of an inert metal conductive material and a non-metallic conductive material; Before the slurry is uniformly coated on the conductive base material, the conductive base material is placed in water and an organic solvent in turn for ultrasonic treatment, wherein the organic solvent includes at least one of methanol, ethanol, acetone and chloroform, and the ultrasonic treatment time is 10-120 minutes.
5. The method according to claim 1, wherein the organic solvent is removed by heating; wherein the heating temperature is 30-150°C and the heating time is 0.5-10h.
6. The method according to claim 1, wherein the micro-electric device comprises a solution tank, electrodes, a power supply, a peristaltic pump, and a stirrer; wherein the aluminum-based lithium adsorbent electrode is connected to the negative electrode of the power supply, and the conductive electrode is connected to the positive electrode of the power supply.
7. The method according to claim 1, wherein the conductive electrode is at least one of an inert metal conductive material and a non-metal conductive material; wherein the inert metal includes gold, silver, platinum, palladium, rhodium, and iridium; and the non-metal conductive material includes graphite, carbon cloth, organic conductive polymer, carbon felt, and conductive ceramics.
8. The method according to claim 1, wherein the total salt concentration in the low-salt lithium-containing system is 1-80 g / L; The cation in the low-salt lithium-containing system is Na + , K + Mg 2+ , Ca 2+ One or more of the following, the anion is Cl - Br - 、F - 、NO2 - 、NO3 - 、CO3 2- 、SO3 2- 、SO4 2- PO4 3- One or more of; The lithium ion concentration in the low-salt lithium-containing system is 0.001-1.0 g / L.
9. The method according to claim 1, wherein the applied high voltage is 20-80V or the applied high current is 5-10A, and the power-on time is 1-10min; The low voltage applied is 0.01-10V or the low current applied is 0.001-1.0A, and the power-on time is 20-120min.
10. The method according to claim 1, wherein the aluminum-based lithium adsorbent electrode is pre-desorbed in a pre-desorption solution before use; The pre-desorption liquid is at least one of deionized water, ultrapure water, lithium-containing solution, ethanol, and propanol; The ratio of aluminum-based lithium adsorbent electrode to pre-desorption solution is 1m 2 :(0.1-4)L; The voltage applied during the pre-desorption is 0.01-10V or the current applied is 0.001-1.0A; the power-on time is 10-60min.